2005
DOI: 10.1016/j.jtcvs.2005.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of extracellular matrix protein expression in the convexity and the concavity of the dilated aorta with bicuspid aortic valve: Preliminary results

Abstract: In bicuspid-associated aortic dilations, an asymmetric pattern of matrix protein expression was found that was consistent with the asymmetry in wall-stress distribution reported previously. Differences exist between patients with stenosis and those with regurgitation in terms of protein expression and content in the aortic wall. Further studies could clarify the relations between these findings and the pathogenesis of aortic dilatation in bicuspid aortic valve patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
106
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 23 publications
(26 reference statements)
9
106
1
5
Order By: Relevance
“…[23][24][25] The present study, however, revealed no significant change in either the adventitial or medial collagen content during TAA formation. Although this may suggest a lack of collagen degradation, given previous results establishing a temporal profile of protease production throughout TAA development, 26 it is more likely that collagen degradation and deposition remain balanced in regard to total content.…”
Section: Analysis Of Taa-induced Structural Changescontrasting
confidence: 82%
“…[23][24][25] The present study, however, revealed no significant change in either the adventitial or medial collagen content during TAA formation. Although this may suggest a lack of collagen degradation, given previous results establishing a temporal profile of protease production throughout TAA development, 26 it is more likely that collagen degradation and deposition remain balanced in regard to total content.…”
Section: Analysis Of Taa-induced Structural Changescontrasting
confidence: 82%
“…The in vitro observed dissimilarities in proliferation and differentiation patterns in fibrosa vs. ventricularis settings could be related to regional differences in blood pressure/volume which concern the ascendant aortic wall [24]. Though these gradients do not have the same magnitude in the pulmonary circulation, a similar flow behaviour is reported for both right and left outflow tracts, where the different fluid mechanics on the ventricular vs. artery side influences the local distribution of the main ECM constituents (elastin and collagens), as well as the least represented proteins (laminin and fibronectin) [24]. In fact, the proteoglycans versican, decorin and biglycan have a significantly higher combinatorial distribution in the ventricularis with a decreasing staining intensity towards the fibrosa, while hyaluronan is strongly expressed in the spongiosa.…”
Section: Discussionmentioning
confidence: 98%
“…No significant differences in the contents of collagen types I, III and IV were found between the region of convexity and concavity of the aortic arch (figure 4) in the aneurysmal and control aortic wall [57]. However, another group showed that type I and III collagens were more markedly reduced in the convexity than in the concavity of the media layer of BAV-dilated ATAs with AVR [66].…”
Section: Effects Of Locationmentioning
confidence: 99%